Perbandingan Metode Preference Selection Index dan Kombinasi Preference Selection Index dan TOPSIS dalam Penilaian Kinerja Karyawan Hotel - Mohammad Aldinugroho Abdullah; Rima Tamara Aldisa (STMIK Budi Darma, 2023)
An employee refers to an individual who works in a company or organization and receives an imbalance in the form of salary or wages for his contribution. Employee Employee refers to work performance obtained by employees in carrying out their duties by meeting the quality and quantity standards expected by the company. Employee performance appraisal contributes to increasing productivity, quality of human resources, employee motivation, decision making, and transparency in the company. Therefore, employee performance appraisal is an important and routine activity in a hotel company environment. Hotel is a place that provides lodging for guests who want to stay temporarily for a certain time. Hotels usually have a variety of facilities and services to meet the needs of guests. In assessing employee performance, several criteria have been determined, namely Quality of Work, Productivity, Communication Skills, Team Collaboration, Problem Solving Ability, Initiative, Creativity, Compliance, Ethics and Self-Development. In this study, we wanted to know the results of the comparison of the implementation of the PSI method to produce weight values ??and rankings with the results of implementing a combination of the PSI and TOPSIS methods, where the PSI method was used for weights and the TOPSIS method for ranking alternatives. The application of this method is carried out to obtain results in evaluating the performance of hotel employees. The research results from a comparison of the application of the PSI method and PSI Cable and TOPSIS produce the same best alternative, namely A7 with a value of 0.9435 with the application of the PSI method and a value of 0.8589 with the application of a combination of the PSI and TOPSIS methods